Documentary "You're on the Air. Now What?" - Marques, S. C. S.; Fernando Sousa (Documentary, 2011)
This movie is the outcome of a desire to revive an idea from the film Photo Wallahs (1991) by Judith and David MacDougall. The idea of giving international exposure to commonly voiceless people, letting them construct audiovisual meanings at their will, was so appealing, that we have decided to develop it into a short film on its own. We made a placard sign written in Bangla and Hindi, installed it at different public locations around Kolkata (capital of West Bengal, India) on different times and waited with the equipment prepared in a fixed shot…